Effect of supplementation with zinc and other micronutrients on malaria in Tanzanian children: a randomised trial. - Jacobien Veenemans; Paul Milligan; Andrew M Prentice; Laura R A Schouten; Nienke Inja; Aafke C van der Heijden; Linsey C C de Boer; Esther J S Jansen; Anna E Koopmans; Wendy T M Enthoven; Rob J Kraaijenhagen; Ayse Y Demir; et al. (PLoS Medicine)
Background It is uncertain to what extent oral supplementation with zinc can reduce episodes of malaria in endemic areas. Protection may depend on other nutrients. We measured the effect of supplementation with zinc and other nutrients on malaria rates. Methods and findings In a 2×2 factorial trial, 612 rural Tanzanian children aged 6-60 months in an area with intense malaria transmission and with height-for-age z-score≤-1.5 SD were randomized to receive daily oral supplementation with either zinc alone (10 mg), multi-nutrients without zinc, multi-nutrients with zinc, or placebo. Intervention group was indicated by colour code, but neither participants, researchers, nor field staff knew who received what intervention. Those with Plasmodium infection at baseline were treated with artemether-lumefantrine. The primary outcome, an episode of malaria, was assessed among children reported sick at a primary care clinic, and pre-defined as current Plasmodium infection with an inflammatory response, shown by axillary temperature ≥37.5°C or whole blood C-reactive protein concentration ≥ 8 mg/L. Nutritional indicators were assessed at baseline and at 251 days (median; 95% reference range: 191-296 days). In the primary intention-to-treat analysis, we adjusted for pre-specified baseline factors, using Cox regression models that accounted for multiple episodes per child. 592 children completed the study. The primary analysis included 1,572 malaria episodes during 526 child-years of observation (median follow-up: 331 days). Malaria incidence in groups receiving zinc, multi-nutrients without zinc, multi-nutrients with zinc and placebo was 2.89/child-year, 2.95/child-year, 3.26/child-year, and 2.87/child-year, respectively. There was no evidence that multi-nutrients influenced the effect of zinc (or vice versa). Neither zinc nor multi-nutrients influenced malaria rates (marginal analysis; adjusted HR, 95% CI: 1.04, 0.93-1.18 and 1.10, 0.97-1.24 respectively). The prevalence of zinc deficiency (plasma zinc concentration <9.9 µmol/L) was high at baseline (67% overall; 60% in those without inflammation) and strongly reduced by zinc supplementation. Conclusions We found no evidence from this trial that zinc supplementation protected against malaria. Trial registration ClinicalTrials.gov NCT00623857